2022
DOI: 10.1126/science.abe7489
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of DNA adenine methylation in eukaryotes using quantitative deconvolution

Abstract: The discovery of N 6 -methyldeoxyadenine (6mA) across eukaryotes led to a search for additional epigenetic mechanisms. However, some studies have highlighted confounding factors that challenge the prevalence of 6mA in eukaryotes. We developed a metagenomic method to quantitatively deconvolve 6mA events from a genomic DNA sample into species of interest, genomic regions, and sources of contamination. Applying this method, we observed high-resolution 6mA deposition in two protozoa. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 57 publications
6
101
2
Order By: Relevance
“…DNA methylation is an important epigenetic modification that plays crucial roles in a variety of cellular processes, such as gene regulation, animal development, X-chromosome inactivation, and chromatin organization 1 4 . Methylation of N6-adenine (6 mA) on DNA was recently discovered to be present in diverse eukaryotes, though it exists at low levels in most of these organisms 5 10 . Unlike the well-studied C5-cytosine methylation (5 mC), the biological functions of 6 mA in eukaryotic genomic DNA is complicated and the various epigenetic mechanisms related to 6 mA remain to be further investigated 11 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is an important epigenetic modification that plays crucial roles in a variety of cellular processes, such as gene regulation, animal development, X-chromosome inactivation, and chromatin organization 1 4 . Methylation of N6-adenine (6 mA) on DNA was recently discovered to be present in diverse eukaryotes, though it exists at low levels in most of these organisms 5 10 . Unlike the well-studied C5-cytosine methylation (5 mC), the biological functions of 6 mA in eukaryotic genomic DNA is complicated and the various epigenetic mechanisms related to 6 mA remain to be further investigated 11 .…”
Section: Introductionmentioning
confidence: 99%
“…(CI, 1-13 p.p.m.) by 6mASCOPE in the two glioblastoma species, suggesting that the 6 mA level in human cells might be overestimated (Kong et al, 2022). Zhang et al 2022b.…”
Section: Prevalence Of 6 Mamentioning
confidence: 93%
“…et al, 2018b). However, 6mASCOPE showed that the 6 mA/A level of VATN sites was 2-3 times higher than that of NATN sites (Kong et al, 2022). Compared to protozoans and metazoans, 6 mA has been less researched in plants and fungi.…”
Section: Prevalence Of 6 Mamentioning
confidence: 95%
See 2 more Smart Citations